Influence of field of view in visual prostheses design: Analysis with a VR system - Sanchez Garcia, Melani; Martínez-Cantín, Rubén; Bermúdez-Cameo, Jesús; Guerrero, José J. (Jornada de Jóvenes Investigadores del I3A, 2020)
In this work, we evaluate the influence of field of view with respect to spatial resolution in visual prostheses. Our system uses a virtual-reality environment based on panoramic scenes and headmounted display which allows users to feel immersed in the scene. Results indicate that, for the design of retinal prostheses, it is better to concentrate the phosphenes in a small area, to maximize the angular resolution, even if that implies sacrificing field of view.